Verify the following 18×{7+(-3)}={18×7}+18×(-3)}
Answers
Answered by
15
18{7+(-3)}=(18x7)+18x(-3)
18{7-3}=126-54
18x4=72
72=72
Hence Verified
18{7-3}=126-54
18x4=72
72=72
Hence Verified
Answered by
7
hi .................... here is your required answer :-
18×{7+(-3)}={18×7}+{18×(-3)}
18×{7-3} = 126+{-54}
18×4 = 126-54
72 = 72
hence , 18×{7+(-3)} = {18×7}+{18×(-3)}
thank you hope this will help you
mark me brainlist please
18×{7+(-3)}={18×7}+{18×(-3)}
18×{7-3} = 126+{-54}
18×4 = 126-54
72 = 72
hence , 18×{7+(-3)} = {18×7}+{18×(-3)}
thank you hope this will help you
mark me brainlist please
Similar questions
Physics,
9 months ago
Math,
9 months ago
Computer Science,
1 year ago
Biology,
1 year ago
Economy,
1 year ago
Computer Science,
1 year ago